Reasons Behind Incomplete Immunization: A Cross Sectional Study at Urban Health Centre of Government Medical College, Aurangabad - Abhijeet Ingale; Dixit JV; Deven Deshpande (Medsci Publications, 2013)
Background: Primary immunization in India is carried out to protect all children against six vaccine preventable diseases; still many children don't receive vaccination at proper age. Objective: To find out reasons for incomplete primary immunization under 2 year children. Material and Method: It was a cross sectional study conducted in field practice area Urban Health Training Centre Government Medical College Aurangabad Maharashtra during Nov to Dec 2011. A house to house survey carried out to find reasons behind incomplete immunization by a group of undergraduate doctors posted at field practice area of Urban Health Centre. Results: 62.24% children received complete immunization till required for their age at proper time according to National immunization schedule while 37.76% children were incompletely immunized. Reasons behind incomplete immunisation were 60.30% children had obstacles 34.35% children lack of motivation & 5.35% children lack of information. Sub reasons behind lack of motivation were ignorance in 82.22% & false beliefs in 17.78%.Sub reasons behind Obstacles were ill health of children in 74.68%, mother and child were out of station in 17.72 % & non availability of the vaccine in 7.60 %. Conclusion: Incomplete immunisation is a major problem of primary immunisation in children. Four out of ten children are incompletely immunised. Chief reasons behind irregularity are obstacles, lack of motivation and lack of information.Present study speak about current immunization status of children and the reasons behind incomplete immunization; It not only gives recommendation and suggestions but also sends a positive message for vaccination in the society.